2009
DOI: 10.1186/1741-7007-7-83
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of blastema formation in regenerating axolotl limbs

Abstract: BackgroundFollowing amputation, urodele salamander limbs reprogram somatic cells to form a blastema that self-organizes into the missing limb parts to restore the structure and function of the limb. To help understand the molecular basis of blastema formation, we used quantitative label-free liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS)-based methods to analyze changes in the proteome that occurred 1, 4 and 7 days post amputation (dpa) through the mid-tibia/fibula of axolotl hind limbs.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
151
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(165 citation statements)
references
References 152 publications
(191 reference statements)
14
151
0
Order By: Relevance
“…However, during muscle dedifferentiation, the expression of many muscle genes, mainly the structural ones, is expected to decrease [28,44-47]. Our Real Time PCR analysis showed that the expression of the late muscle genes car (alpha-cardiac actin) and myh4 (myosin heavy chain 4) was 5-fold lower in the 3 dpa distal tail stump compared to the 0 dpa distal stump (Figure 4a).…”
Section: Resultsmentioning
confidence: 97%
“…However, during muscle dedifferentiation, the expression of many muscle genes, mainly the structural ones, is expected to decrease [28,44-47]. Our Real Time PCR analysis showed that the expression of the late muscle genes car (alpha-cardiac actin) and myh4 (myosin heavy chain 4) was 5-fold lower in the 3 dpa distal tail stump compared to the 0 dpa distal stump (Figure 4a).…”
Section: Resultsmentioning
confidence: 97%
“…Differentially expressed genes within our intervals and involved in metabolism include Cs, Rnf7 and Becn1. We focused on this group because of previous studies showing the importance of aerobic glycolysis and mitochondrial variations in MRL ear hole regeneration (Sachadyn et al, 2008;Naviaux et al, 2009) and the role of glycolytic enzymes during amphibian regeneration (Schmidt, 1958, Rao et al, 2009). We examined Cs or citrate synthase, a Kreb cycle enzyme and structural mitochondrial protein found in the mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The first gene we examined in this group, Kif23, is a motor molecule known to be involved in cytokinesis (Nislow et al, 1992;Raich et al, 1998;Neef et al, 2006), a process important in axolotl (Rao et al, 2009, Heber-Katz et al, 2013 and zebrafish regeneration (Poss et al, 2002(Poss et al, , 2004. Kif23, also known as MKLP1, is part of a critical complex formed at the midzone or midbody and associates with CYK-4 in the central spindlin (Glotzer, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…43 Consistent with this scenario is the fact that the gene encoding AGP supports the growth of the blastema to fingerbud stages when electroporated into the tip of a denervated limb during histolysis and dedifferentiation. 42 Other important signaling molecules for blastema formation and growth are Fgf-2, 8, 10, BMPs and Wnt, 3,44 but how they are integrated with AGP is not known.…”
Section: Amphibians As Models To Study Limb Regenerationmentioning
confidence: 99%
“…Proteomic analysis in our laboratory revealed high levels of the centrosomal protein EVI5 throughout blastema formation in the axolotl. 44 EVI5 functions in mammalian cells to stabilize the Emi1 protein, which prevents cells from entering the mitotic phase of the cell cycle while they replicate DNA. 62 Both EVI5 and Emi1 are destroyed at G 2 , allowing cells to enter mitosis.…”
Section: Radiograms Of Control (A B A' and B') And Ra-treated (Cmentioning
confidence: 99%